Machining with abrasives - Jackson, Mark J. (Springer US, 2011)
Abrasive machining is one of the most important processes used in manufacturing engineering. It is key to removing unwanted material, as well as to obtain the desired geometry and surface quality in manufacturing. "Machining with Abrasives" discusses the fundamentals and advances in the abrasive machining processes, and provides a complete overview of newly-developing areas in the field. Abrasive machining processes where material is removed from a work piece using a multitude of hard angular abrasive particles or grains which may or may not be bonded to form a tool are discussed at length. Also covered are: -Laser-based and diamond dressing techniques -High-efficiency deep grinding -Peel grinding and new grinding wheels -A comprehensive discussion of the latest in micro- and nano-grinding "Machining with Abrasives" collects contributions from leading researchers in the field, and is a must-read for any researcher or engineer working in manufacturing engineering.